Integrating Climate Change Education in English Lessons and P5 Projects in Junior High Schools - Nurhaliza, Salsabila; Silvhiany, Sary; Inderawati, Rita (Universitas Pendidikan Mandalika, 2024)
English lessons are being used to teach about climate change, combining language learning with environmental education. This aligns with the Pancasila Student Profile (P5) framework, which focuses on character development and global awareness. This research investigates the integration of climate change education into the P5 Project and English language lessons in junior high schools in South Sumatra, Indonesia. It examines the familiarity and willingness of teachers to incorporate climate change topics into their teaching. The study uses a qualitative research design, conducting interviews with 11 English teachers to explore their perspectives and experiences. The findings reveal that while some schools have implemented projects that promote environmental awareness and sustainability, such as recycling initiatives, there is a lack of systematic integration of climate change education into the English curriculum. Teachers expressed a willingness to teach about climate change but lacked Â formal training. The research highlights the need for comprehensive strategies to integrate environmental literacy into language learning and the importance of teacher preparation in effectively implementing climate change curricula. The study contributes to the understanding of how to enhance climate change education at the junior high school level, particularly in the context of South Sumatra, and emphasizes the role of teachers in fostering environmental stewardship among students.